EXAMINING MSME STRATEGIES IN THE CULINARY SECTOR TO SURVIVE IN THE NEW NORMAL ERA - Ni Wayan Candra Dewi; Ida Bagus Teddy Prianthara (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
MSMEs in the culinary field must begin to adapt to digitalization if they want their businesses to survive and advance in this new normal era. This study aims to analyze the strategy of MSMEs in the culinary field to survive in the new normal era. This research is descriptive qualitative research. The research location was conducted in Tabanan Regency, Bali Province. The sample in this study was 4 MSMEs in the culinary field, which were taken purposively. The data collection technique was done by interview, observation, and documentation. Data analysis using source triangulation. The results of the study state that the grant provided by the government has significant benefits for MSME business owners to maintain their business in the new normal era. The digital marketing strategy has a huge role in the sustainability of an MSME business in the new normal era. Technology that supports the effectiveness of the performance of culinary MSMEs, where they state that the activities carried out in their business can be effective and satisfy customers, they use supporting technology to maximize the effectiveness of their business. Culinary SMEs have also carried out improvements in terms of service to consumers in the Tabanan area. All informants, in this case, stated that to improve their services to consumers, they provide various menu choices for their businesses so that consumers feel satisfied shopping for their businesses. Suggestions and guidelines for further research are expected that further researchers can expand the scope of research and also the type of field studied so that they can provide new findings from different perspectives